IMPROVING BUSINESS PERFORMANCE WITH ISO 9001: A REVIEW OF LITERATURE AND BUSINESS PRACTICE - Bakator, Mihalj; Ćoćkalo, Dragan (The European Journal of Applied Economics, 2018)
This paper studies the impact of the ISO 9001 on business performance. Inaddition, the impact on business performance metrics is also investigated.These metrics are product, and service quality, customer satisfaction,financial performance, and operational performance. In the process ofselection, 25 out of 110 papers were chosen for further analysis. The sumof samples is 6605. Therefore, the paper has moderate significance andmoderate contribution in the domain of ISO 9001 certification. The keyfindings of this paper indicated that ISO 9001 certification can improveoperational performance, customer satisfaction, financial performance,and overall business performance. However, negative impact of ISO 9001on the mentioned constructs is also noted. For practical implication,companies may use this systematic review as a tool which may help indecision making regarding ISO 9001 standards certification or overallbusiness performance improvement.